c - Miles, Becky (Essex, United Kingdom : Miles Kelly Publishing Ltd, 2018)
Children will love these charming princess stories. Both traditional and modern tales are told in a clear and engaging way to encourage reading
Keywords: Folk literature, English; Fairy tales, English; Children's stories